Sifat Fisikokimia dan Fungsional Pati Buah Aibon (Brugueira gymnorhiza L.) - Sarungallo, Zita Letviany; Santoso, Budi; Tethool, Eduard Frasisco (Jurnal Natur Indonesia, 2010)
The aim of this research was to evaluate the physicochemical and functional properties of aibon (Brugueiragymnorhiza L.) starch. Research’s results show that the form of aibon starch granule was ellips like kidney, withsize of 5-4.5 μm, has high amylose content of 32.35%, and gelatinization temperature of 85.5-95oC. It also has highsolubility (7oBrix) and swelling powered of 14.83% at 90oC. Pasting behavior of starch suspension (6.5%, w/v)shows the initial pasting temperature at 85.5oC and peak viscosity 200 BU reached at 93oC. The wide range ofgelatinization temperature makes aibon starch resistant to high heat temperature. Functional characters thatmake aibon starch important for industrial application are its non-adhesive and un-sticky paste, increasing viscositywhile it was heated, unstable gel forming, and low stability to freezing-thawing cycle. Aibon starch also haspotential usage for carbohydrate base products that need starch which has heat resistant granule but does notneed starch that has high viscosity paste.